Het Duitslandbeeld en het Nederlandbeeld van scholieren in de grensregio - Pollemans, Robine (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Deutschlandbild; Euregio Rhein-Waal; Niederlandebild; Schüler; Schüleraustausch

Aan de Hollands-Duitse stamtafel. Het Consulaat der Nederlanden in Kleef in roerige tijden 1920–1960 - Brauer, Jan (Gelderland grensland. 2000 jaar verdeeld en verbonden, 2016)
Keywords: Grenzgebiet; Kleve (Kreis Kleve); Konsulat

Grenskloosters en de naderende Klostersturm. Religieuzen en de eerste confrontaties met de nazi-staat langs de Nederlandse grens tussen 1930 en 1940 - Brauer, Jan (Dienstbaar onder vuur. Religieuzen en de Tweede Wereldoorlog, 2016)
Keywords: Grenzgebiet; Kloster; Orden

Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Spanning aan de grens in Belfeld. De familie Feller achtervolgd door de Gestapo, 1936–1945 - Brauer, Jan (Jaarboek Maas- en Swalmdal, 2015)
Keywords: Venlo

Spanning aan de grens in de regio Venlo. Grensincidenten, nazi´s en verzet midden jaren ´30 - Brauer, Jan (Venlose Katernen, 2015)
Keywords: Venlo

Over de grens. Verzet en verraad in de grensregio Nijmegen-Kleef 1930–1940 - Brauer, Jan (Jaarboek Numaga, 2014)
Keywords: Kleve (Kreis Kleve); Nimwegen

Gevaarlijke grenzen. Gelre, Gulik en Kleef in hun conflicten en bondgenootschappen met de Bourgondische vorsten 1473–1543 - Groustra-Werdekker, Aafje H. (Recht, Religion, Gesellschaft und Kultur im Wandel der Geschichte. Ferculum de cibis spiritualibus. Festschrift für Dieter Scheler, 2008)
Keywords: Burgundische Niederlande; Herzogtum Jülich; Internationale Politik; Staat Geldern; Staat Kleve

Die kartographiehistorischen Forschungen von Gerhard Aymans im Rhein-Maas-Gebiet - Krings, Wilfried (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Niederrhein-Gebiet; Rhein-Maas-Gebiet

Die Bedeutung der Forschung von Prof. Dr. Gerhard Aymans für das niederländische Nordlimburg - Renes, Hans; Storms, Martijn (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Kataster; Kleve (Kreis Kleve)

Tastbaar verleden. Objecten uit de grensregio = Erfassbare Vergangenheit. Objekte aus der Grenzregion - Lenders, Wiel P.H.; Kersten, Julie; Trost, Ralph (Nationaal Bevrijdingsmuseum 1944–1945, 2006)
Keywords: Euregio Rhein-Waal; Sachkultur; Zweiter Weltkrieg

Schmuggeln - einst für Grenzanrainer oft überlebenswichtig - Rühl, Hans (Kalender für das Klever Land, 2006)
Keywords: Grenzgebiet; Kleve (Kreis Kleve); Schmuggel

„... an villen Orteren von allerseidtz Kriegsfolck verdorben ...“. Die Folgen des Spanisch-Niederländischen Krieges (1566–1609) für die Grafschaft Mark - Kloosterhuis, Jürgen (Der Märker, 1983)
Keywords: Achtzigjähriger Krieg; Grafschaft Mark; Herzogtum Jülich-Berg; Jülich-Kleve-Berg